2006
DOI: 10.1111/j.1540-8159.2006.00426.x
|View full text |Cite
|
Sign up to set email alerts
|

The Risk Profile for Obstructive Sleep Apnea Does Not Affect the Recurrence of Atrial Fibrillation

Abstract: Long-term pacemaker recording of AF recurrence, AF burden, and its circadian distribution is similar in patients with paroxysmal AF at high risk for OSA and those at low risk for OSA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 22 publications
1
1
0
1
Order By: Relevance
“…The frequency and duration of paroxysmal AF events was similar in patients with and without SDB that is in agreement with previous reports in a larger population of patients with permanent PM 13 . A low prevalence of overall arrhythmic events similar to that observed in our study has been reported previously in a larger cohort of patients aged >65 years with SDB 14 …”
Section: Discussionsupporting
confidence: 93%
“…The frequency and duration of paroxysmal AF events was similar in patients with and without SDB that is in agreement with previous reports in a larger population of patients with permanent PM 13 . A low prevalence of overall arrhythmic events similar to that observed in our study has been reported previously in a larger cohort of patients aged >65 years with SDB 14 …”
Section: Discussionsupporting
confidence: 93%
“…Except for a few studies showing the lack of increased incidence of OSA in AF patients, the majority of studies demonstrated otherwise. 26,27 For example, Gami et al prospectively studied consecutive patients undergoing electrocardioversion for AF (n=151) and consecutive 312 patients referred to a general cardiology practice without a past or current history of AF (n=312). 7 They showed the proportion of patients with OSA was significantly higher in the AF group than in the general cardiology group (49 % versus 32 %; p=0.0004).…”
Section: Association Between Atrial Fibrillation and Obstructive Sleementioning
confidence: 99%
“…Bazı çalışmalarda bradikardi, atriyoventriküler blok, atriyum fibrilasyonu, VEA ve ventrikül taşikardisi gibi aritmiler ile TUAS arasında ilişki gösterilirken, bazı çalışmalarda ise aritmiler ile TUAS arasında herhangi bir ilişki bulunmamıştır. [17,[26][27][28][29][30] Sleep Heart Health çalışmasında, TUAS hastalarında ventrikül taşikardisi ve süreksiz ventrikül taşikardisi sıklığında artış gösterilmiştir. [17] Çalışmamızda da TUAS grubunda saptanan artmış AEA ve VEA sıklığı bu verileri desteklemektedir.…”
Section: İstatistiksel Değerlendirmeunclassified